STUDY OF FERRIMAGNETIC MIXED SPIN-3/2 AND SPIN-5/2SYSTEM USING ISING MODEL - Ibrahim, Fuad; Khidhir, Ali; Mohamed, Hadey; Mohamed, Hadey (Iraqi Journal of Science, 2024)
The mixed spin-3/2 and spin-5/2 Ising ferrimagnetic system with differentanisotropies has been investigated using the mean field approximation (MFA) .Thephase diagram of the system has also been discussed in the anisotropy dependenceof transition temperature. It is found that a reentrant ferrimagnetic phenomenon inthe ordered system depends strongly on the anisotropy of the mixture.